Innovation rankings: Good, bad or revealing? - Yuezhou Cai; Aoife Hanley (Kiel Institute for the World Economy (IfW), 2013)
The standard indicators used to compare cross-country innovation are in the Global Competitiveness Report (GCR). But there are problems with aggregation and response bias with these largely self-reported measures (Hollanders and van Cruysen, 2008). We propose a theory-based metric using Data Envelopment Analysis which corrects for sample bias and considers Returns to Scale. The derived ranking compares well to components of the GCR. Moreover, in second-stage estimations, our corrected efficiency score correlates well with standard Growth Theory indicators.
Keywords: C61; C14; O38; 330; Data Envelopment Analysis; Efficiency Indicators; Global Competitiveness Report